Educational Sex Segregation in Rajasthan - Shah, Meenal (Mathematical Statistician and Engineering Applications, 2018)
Sex segregation in education is an important factor, responsible for occupational sex segregation and further wage gap. The origin of the occupational sex segregation must be sought in the school system’s first branching point. It is hypothesized that the educational opportunities, choices and attainment for girls differ significantly from those of boys. The analysis is based on secondary data obtained from Census of India, Board of Secondary Education and Directorate of College Education. It is found, that illiteracy among the female population is higher. As expected the level of completed education of female population is much lower than the level attained by male population. Female population prefers arts while males prefer science and commerce. Share of girls is higher in non-technical courses. Among professional and technical courses, teaching is most popular among females.